(untitled) (Research, Society and Development, 2021)
This study aims to understand the perception of nurse preceptors regarding the humanization of care, in the context of the training of nurses, in a teaching hospital. It is a descriptive research, with a quanti-qualitative approach, carried out through the application of an online form whose sample was composed of 17 nurse tutors who work in inpatient units. As for the profile, they are female (76.5%), 31 to 40 years old (82.3%), they work from 0 to 1 year in the current sector, 5 to 10 years of training (82.3%), lato sensu specialization (94.1%), attended residency (35.2%) and studied master’s degree (23.5%), has research experience (52.9%), has experience with traditional teaching at technical level (47.0 %), have no experience with active methodologies (47.0%), have no experience with Distance Education (41.1%), have experience with tutoring (52.9%) and were tutors in 2020 (64.7%). 70.6% claim to know the term "Humanization of Care" and described this concept as an integral understanding of the human being (100%), empathy (100%) and respect (100%), human treatment (88.2%) and ambience (76.5%). They affirm that the humanization of patient care in the context of the training of nurses translates into learning to be developed by the student in permanent and reflective contact with the real situations of daily work (82.4%) and rated 4 for their practice regarding the humanization (70.6%), out of a total of 5 points. It is believed that this research is relevant as a way of analyzing how preceptorship influences the construction of the nursing student / student humanization process.